On Brazilian Cinema: A Portrait of Director and Producer Walter Salles - Korfmann, Michael; Kepler, Filipe Kegles (Contingentia, 2010)
Walter Salles is probably the most widely known Brazilian director and producer. This article offers a portrait of his work over the last two decades as part of the cinematic and cultural changes that took place in Brazil. It starts with a historical overview of Brazilian film history and will then take a closer look at the films directed by Salles and his activities as producer. By looking at the evolution of the Brazilian film industry in the last ten to fifteen years in terms of market structures as well as aesthetic qualities, two major references become apparent: the more (but not only) commercial oriented productions of Globo Filmes, which often meet public taste and rely on a well-proven television language; second, the movies of Walter Salles as well as the films produced by Videofilmes, a company run and founded in 1987 by him and his brother, the documentarist João Moreira Salles. Videofilmes not only fosters many of the somewhat marginal, smaller film projects, but also serves as support for more artistically orientated movies.